PERLINDUNGAN HUKUM BAGI KORBAN PERKOSAAN ANAK DIBAWAH UMUR (STUDI KASUS PADA DP3A KOTA SEMARANG) - Ulya Fardani; Wenny Megawati (HUKMY : Jurnal Hukum, 2025)
This research focuses on legal protection for minor rape victims, with a case study conducted at the Semarang City Women's Empowerment and Child Protection (DP3A) Service. The background to this research problem stems from the high number of cases of sexual violence against minors and the need for effective legal protection to protect children's rights. The problems formulated include the form of legal protection provided to victims and the efforts made by DP3A to provide this protection. The aim of this research is to explain the existing forms of legal protection and the efforts that have been made to protect minor victims. It is hoped that the benefits of this research will provide theoretical insight for the development of legal science, as well as become a practical reference for the community and related parties in applying legal protection regulations for victims of child sexual violence.